Perception of Computer Graphics Characters in Groups with Skin Color Diversity - Araujo, Victor Flávio de Andrade; Schaffer, Diogo Hartmann Muller; Costa, Angelo Brandelli; Musse, Soraia Raupp (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
This paper aims to assess the human perception of groups about charisma, comfort and realism in relation to black and white skin colors of characters created with Computer Graphics (CG) in different media, such as movies, games, animations, simulations, among others. We created a form that contained images of groups of CG characters with black and white skin colors, and asked participants to rate perceived comfort, charisma and realism. After that, we compared these results with data collected from related work. The results indicated that people can feel comfortable, and observe charisma similarly to CG characters with black and white skin colors.